2023
DOI: 10.1097/md.0000000000033432
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as prognostic markers in patients with extensive-stage small cell lung cancer treated with atezolizumab in combination with chemotherapy

Abstract: Atezolizumab is now the standard treatment for extensive-stage small cell lung cancer (ES-SCLC). Herein, we investigated the prognostic role of inflammatory markers in patients treated with atezolizumab plus chemotherapy and evaluated the efficacy and safety of adding atezolizumab to chemotherapy for patients with ES-SCLC and prognostic and predictive factors as a real-life experience. This retrospective study included 55 patients who received front-line atezolizumab with etoposide plus platin regimen for ES-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Of potential prognostic importance is the patient’s early tumour response, since early tumour shrinkage/response is associated with improved survival in patients with ES-SCLC [ 14 16 ], although our patient also had a number of characteristics that could have contributed to his long-term survival, including age < 65 years [ 17 , 18 ] and good performance status [ 16 , 19 23 ]. Further, his neutrophil-to-lymphocyte ratio (2.05) was consistent with that considered to be prognostic for better survival (a ratio of ≤ 3.43), as reported in a study that investigated the prognostic role of inflammatory markers in patients with ES-SCLC who were treated with atezolizumab plus chemotherapy [ 24 ]. However, our patient also had risk factors for reduced survival, including male gender [ 16 ] and bone metastasis [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 78%
“…Of potential prognostic importance is the patient’s early tumour response, since early tumour shrinkage/response is associated with improved survival in patients with ES-SCLC [ 14 16 ], although our patient also had a number of characteristics that could have contributed to his long-term survival, including age < 65 years [ 17 , 18 ] and good performance status [ 16 , 19 23 ]. Further, his neutrophil-to-lymphocyte ratio (2.05) was consistent with that considered to be prognostic for better survival (a ratio of ≤ 3.43), as reported in a study that investigated the prognostic role of inflammatory markers in patients with ES-SCLC who were treated with atezolizumab plus chemotherapy [ 24 ]. However, our patient also had risk factors for reduced survival, including male gender [ 16 ] and bone metastasis [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 78%
“… 16 However, Yasin et al found that NLR was associated with poor prognosis in 55 extensive-stage SCLC patients who received front-line atezolizumab with etoposide plus platin regimen. 17 The difference of two studies might be due to sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is also supported by previous studies that have demonstrated the value of combining multiple inflammatory markers to improve prognostic stratification in patients with SCLC. 6 , 47 , 48 , 49 …”
Section: Discussionmentioning
confidence: 99%